2006
DOI: 10.1200/jco.2006.06.1440
|View full text |Cite
|
Sign up to set email alerts
|

Phase III Trial Comparing 4-Day Chronomodulated Therapy Versus 2-Day Conventional Delivery of Fluorouracil, Leucovorin, and Oxaliplatin As First-Line Chemotherapy of Metastatic Colorectal Cancer: The European Organisation for Research and Treatment of Cancer Chronotherapy Group

Abstract: Both regimens achieved similar median survival times more than 18 months with an acceptable toxicity. The chronomodulated schedule produced a survival advantage over FOLFOX in men. The strong sex dependency of optimal scheduling of fluorouracil, leucovorin, and oxaliplatin calls for translational investigations of determinants related to the patient's molecular clock.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

4
182
0
5

Year Published

2009
2009
2020
2020

Publication Types

Select...
7
2

Relationship

3
6

Authors

Journals

citations
Cited by 201 publications
(191 citation statements)
references
References 34 publications
4
182
0
5
Order By: Relevance
“…8,[36][37][38]43,44 It is interesting to note that the downstaging of unresectable liver metastases with modern neoadjuvant chemotherapy regimens has allowed potentially curative resection in up to 30% of patients across published series. 45 Furthermore, a recent analysis revealed that pathologic a complete response to chemotherapy is a major determinant of long-term survival and cure in patients with metastatic CRC.…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…8,[36][37][38]43,44 It is interesting to note that the downstaging of unresectable liver metastases with modern neoadjuvant chemotherapy regimens has allowed potentially curative resection in up to 30% of patients across published series. 45 Furthermore, a recent analysis revealed that pathologic a complete response to chemotherapy is a major determinant of long-term survival and cure in patients with metastatic CRC.…”
Section: Discussionmentioning
confidence: 99%
“…36,37 Nevertheless, a recent, large, randomized trial using individual dose escalation revealed a survival advantage in men but not in women who received chronotherapy. 38 The combination of both HAI and chronomodulated delivery of multidrug regimens could further improve the therapeutic index of cytotoxic chemotherapy in patients who have liver metastases from CRC. The peak time of chronomodulated irinotecan at 5 AM corresponded to low proportion of S-phase cells in healthy tissues and to high Bcl-2 messenger RNA expression in oral mucosa and, presumably, in other healthy tissues.…”
mentioning
confidence: 99%
“…Patients in Cohort I received FL or FLO chronotherapy as first or second line chemotherapy Levi et al, 2007;Curé et al, 2002). Patients in Cohort II received first line chronoFLO or FOLFOX for metastatic disease (Innominato et al, 2009a;Giacchetti et al, 2006). Irinotecan-based chemotherapy was administered to 39.4% of the patients in Cohort III, and in none of the patients in either Cohort I or II.…”
Section: Patient Cohorts and Treatment Regimensmentioning
confidence: 99%
“…Of note, several prognostic factors have been found in previous clinical trials [2][3][4][5][6][7][8][9][10][11][12][13][14][15]. These were patient characteristics such as performance status (PS), age, sex, weight loss, biological variables such as white blood cell count (WBC), serum alkaline phosphatase (ALP) level, serum lactate dehydrogenase (LDH) level, serum carcino-embryonic antigen (CEA) level, or tumor characteristics like the number of metastatic sites or liver involvement (Table 1).…”
Section: Introductionmentioning
confidence: 99%